Pengaruh Pupuk Organik Cair NASA terhadap Nitrogen Bintil Akar dan Produksi Macroptilium Atropurpureum - M. Nur Husin (Jurnal Agripet, 2012)
The effect of liquid organic fertilizing NASA on nitrogen root nodule and production of siratro ABSTRACT. A study was carried out in Experimental Farm and Laboratory for Animal Nutrition of the Faculty of Agriculture in Syiah Kuala University, Darussalam Banda Aceh to know the dose of liquid organic fertilizing (LOF) NASA on nitrogen root nodule and production of Siratro plants. The study use pot (plastic bag) containing 15 kg of soil. The soil type was of kind of Alluvial. Experimental design was of Completely Randomized Design (CRD). Treatment with LOF NASA was of 0.00 cc/l water, 2.50 cc/l water, 5.00 cc/l water, 7.50 cc/l water, and 10 cc/l water. Result showed that a maximum nitrogen root nodule of Siratro 8.54 mg/m2/day and maximum dry matter production of Siratro 2.26 g/m2/day was founded at 10 cc/l water LOF NASA.